Navigating Multilingual Communication in the Digital Age: The Role of Artificial Intelligence in Translanguaging - Patrick Mthethwa (Scientia Publica Media, 2026)
Advancements in technology, including the development of Artificial Intelligence (AI) tools, have renewed interest in translanguaging, with a particular focus on AI’s role in this context. AI is continuously and steadily developed to perform human tasks, such as thinking and responding to prompts. As a result, the transformative nature of AI has significantly impacted the education sector in ways never experienced before. This study explored how AI natural language processing (NLP) models and AI-powered tools lay a foundation for the translanguaging of Nguni languages. The study explored how the language translation tool, language learning tool, content creation tool, speech recognition tool, sentiment analysis tool, and educational tool are integral to the translanguaging discourse of the Nguni languages: isiNdebele, isiXhosa, isiZulu, and Siswati. The study was classroom-based action research in a certain South African University. Fifteen (15) participants in the study were a cohort in a postgraduate class. Data were collected using face-to-face interviews and analyzed using Thematic Content Analysis (TCA). The findings revealed that the convergence of AI and translanguaging offers benefits to learners, and that some AI-powered tools support translanguaging of the Nguni languages, although there are inequalities within the Nguni languages, with some being more dominant than others. The study also noted that the complexities embedded in the typologies of the Nguni languages in terms of suprasegmental notations and diction pose an enormous challenge in using AI for translanguaging. These findings have implications for the development of AI-powered tools appropriate for addressing the linguistic dichotomies among the Nguni languages.